Occupational Medicine and Total Worker Health®: from preventing health and safety risks in the workplace to promoting health for the total well-being of the worker - Iavicoli, Ivo; Spatari, Giovanna; Chosewood, L. Casey; Schulte, Paul A. (La Medicina del Lavoro, 2022)
SummaryThe COVID-19 pandemic has highlighted the importance of Public Health interventions for global social and economic development. Still, the community’s well-being depends on each individual’s health. In addition to pandemics, health conditions can be altered by chronic degenerative diseases, aging, disabilities, and work. Personal behaviors such as poor nutrition, lack of physical activity, tobacco use, excessive alcohol consumption, and drug use can also affect health and safety at work. In the last twenty years, we have witnessed rapid changes in the nature of work, workplace and workforce. In parallel, there is increasing attention to fatigue, psychosocial risks and the achievement of decent, sustainable and healthy work as societal goals. Consequently, in 2011, NIOSH developed Total Worker Health®, a holistic approach to worker well-being to help improve worker health and safety. More recently, in Italy, the Ministry of Health has provided for the preparation of projects according to the “Total Worker Health (TWH)” approach in the National Prevention Plan for the five years 2020-2025. As indicated by the Ministry, the strategic role of the occupational physician is fundamental, being the only figure of occupational safety and health professionals able to integrate the health and safety of workers with their well-being to reach the Total Worker Health.